High-temperature-resistant diaphragm for lithium battery and preparation method of high-temperature-resistant diaphragm
By forming a porous modified layer on the lithium-ion battery separator, using specific materials and electrospinning method, the thermal stability of the separator at high temperatures is solved, and the safety performance of the lithium battery is significantly improved.
Patent Information
- Application Number
- CN202411447630.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing lithium-ion battery separators have poor thermal stability at high temperatures, which are prone to thermal shrinkage or melting, resulting in short circuits inside the battery and affecting safety.
Polypropylene separators are used and porous modified layers are formed on their surfaces. Polyimide, cage polysilsesquioxane, alumina and silica fibers are used to combine arginine modified carbon nanotubes and oxides. Zirconium, the first and second modified layers are formed by electrospinning, and the thermal stability of the separator is enhanced.
It significantly improves the high temperature resistance and thermal stability of the lithium battery separator, extends the battery life and improves safety performance.
Smart Images

Figure CN119171011A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a high temperature resistant diaphragm for lithium batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long life, and no memory effect. They are widely used in mobile phones, laptops, electric vehicles and other fields. With the continuous expansion of application fields, the safety issues of lithium-ion batteries have received more and more attention. As an important component of lithium-ion batteries, diaphragms play a key role in the safety of lithium-ion batteries. For diaphragms, the commonly used polyolefin diaphragms have a low melting point and poor thermal stability. Once the battery temperature is too high, it is easy to shrink or even melt, causing a short circuit inside the battery.
[0003] Application Contents
[0004] The present application has been made in view of the above-mentioned problems, and an object of the present application is to provide a high temperature resistant separator for a lithium battery, the separator having excellent high temperature resistance performance.
[0005] Specifically as follows, the first aspect of the present application provides a high temperature resistant diaphragm for a lithium battery, comprising a polypropylene diaphragm body;
[0006] A first modified layer is provided on one side of the polypropylene diaphragm body;
[0007] A second modified layer is provided on the other side of the polypropylene diaphragm body;
[0008] The first modified layer includes the following preparation materials:
[0009] Polyimide, cage-type polysilsesquioxane, alumina, and silica fibers;
[0010] The second modified layer includes the following preparation materials:
[0011] Polyethylene terephthalate, arginine-modified carbon nanotubes, and zirconium oxide.
[0012] According to one of the technical solutions of this application, at least the following beneficial effects are achieved:
[0013] In the present application, a first modified layer and a second modified layer are provided on the film of the polypropylene diaphragm; the polyimide in the first modified layer and the polyethylene terephthalate in the second modified layer have excellent high temperature resistance, thereby improving the heat resistance effect of the diaphragm;
[0014] In the present application, inorganic particles (zirconia, alumina and silica fibers) are added to the modified layer, and a porous modified layer is formed by the inorganic particles and the matrix polymer (polyimide or polyethylene terephthalate); at the same time, the rigidity of the inorganic particles in the porous modified layer is used to support the diaphragm, which enables the diaphragm to obtain excellent thermal stability; in the present application, alumina particles and silica fibers are used to form a point-line network to further improve the thermal stability of the diaphragm; arginine-modified carbon nanotubes and zirconium oxide are used to form a point-line network to further improve the thermal stability of the diaphragm.
[0015] At the same time, the present application grafts arginine onto the surface of carbon nanotubes. The grafting of arginine can simultaneously introduce a large number of polar groups such as hydroxyl, carboxyl, and amide onto the surface of carbon nanotubes, which is beneficial to improving the dispersibility of carbon nanotubes in the modified layer, thereby helping to improve the stability of the point-line network; thereby further improving the thermal stability of the diaphragm.
[0016] In the present application, cage silsesquioxane is added to polyimide. The cage silsesquioxane has functional groups that can interact with amino groups, so as to improve the dispersibility of the cage silsesquioxane in the polyimide, thereby promoting the dispersibility of the inorganic particles in the polyimide and further improving the thermal stability of the separator.
[0017] According to some embodiments of the present application, the cage-type polysilsesquioxane is octamaleamic acid cage-type silsesquioxane.
[0018] According to some embodiments of the present application, the first modified layer includes the following preparation raw materials in parts by weight:
[0019] 100 parts of polyimide, 4 to 6 parts of cage-type polysilsesquioxane, 1 to 3 parts of alumina and 2 to 4 parts of silica fiber.
[0020] According to some embodiments of the present application, the raw materials for preparing the first modified layer also include a solvent.
[0021] According to some embodiments of the present application, the second modified layer includes the following preparation raw materials in parts by weight:
[0022] 100 parts of polyethylene terephthalate, 10 to 20 parts of arginine-modified carbon nanotubes and 3 to 5 parts of zirconium oxide.
[0023] According to some embodiments of the present application, the raw materials for preparing the second modified layer also include a solvent.
[0024] According to some embodiments of the present application, the thickness of the polypropylene diaphragm body is 5 μm to 30 μm.
[0025] According to some embodiments of the present application, the thickness of the first modified layer is 1 μm to 4 μm.
[0026] According to some embodiments of the present application, the thickness of the second modified layer is 1 μm to 4 μm.
[0027] According to some embodiments of the present application, the arginine-modified carbon nanotubes include the following preparation raw materials:
[0028] Carbon nanotubes, nitric acid, thionyl chloride, and arginine.
[0029] According to some embodiments of the present application, the particle size of the aluminum oxide is 20 nm to 50 nm.
[0030] According to some embodiments of the present application, the silica fiber includes the following preparation raw materials:
[0031] PVA solution and silica sol.
[0032] According to some embodiments of the present application, the mass fraction of the PVA solution is 11% to 13%.
[0033] According to some embodiments of the present application, raw materials for preparing the silica sol include tetraethoxysilane and a catalyst.
[0034] According to some embodiments of the present application, the mass ratio of the PVA solution to the silica sol is 1:0.9-1.1.
[0035] The second aspect of the present application discloses a method for preparing a high temperature resistant separator for a lithium battery according to the first aspect of the present application, comprising the following steps:
[0036] The first modified layer and the second modified layer are formed on the surface of the polypropylene diaphragm body by using an electrostatic spinning method.
[0037] According to some embodiments of the present application, the method for preparing arginine-modified carbon nanotubes comprises the following steps:
[0038] S1, mixing carbon nanotubes and nitric acid solution and subjecting them to hydrothermal reaction to obtain carboxylated carbon nanotubes;
[0039] S2, mixing the carboxylated carbon nanotubes and thionyl chloride and reacting them to obtain acyl chloride carbon nanotubes;
[0040] S3, mixing the acyl chloride carbon nanotubes, arginine, dicyclohexylcarbodiimide and a solvent and reacting them.
[0041] According to some embodiments of the present application, the mass volume ratio of the carbon nanotubes and the nitric acid solution is 1 g: 50 mL to 100 mL.
[0042] According to some embodiments of the present application, the temperature of the hydrothermal reaction in step S1 is 110°C to 130°C.
[0043] According to some embodiments of the present application, the mass volume ratio of the carboxylated carbon nanotubes and thionyl chloride is 1 g: 100 mL to 200 mL.
[0044] According to some embodiments of the present application, the reaction temperature in step S2 is 80°C to 90°C.
[0045] According to some embodiments of the present application, the mass ratio of the chlorinated carbon nanotubes to arginine is 1:1-2.
[0046] According to some embodiments of the present application, the mass ratio of the chlorinated carbon nanotubes to dicyclohexylcarbodiimide is 1:0.2-0.3.
[0047] According to some embodiments of the present application, the temperature of the reaction in step S3 is 60°C to 70°C.
[0048] According to some embodiments of the present application, the spinning voltage selected in the electrospinning method is 5 kV to 10 kV. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0050] Figure 1 It is a schematic diagram of the cross-sectional structure of the high temperature resistant diaphragm in the embodiment of the present application.
[0051] Description of Figure Numbers:
[0052] 100. Polypropylene diaphragm body; 101. First modified layer; 102. Second modified layer.
[0053] The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0055] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.
[0056] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.
[0057] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0058] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0059] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0060] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0061] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0062] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0063] The properties of some raw materials in this application are as follows:
[0064] Carbon nanotubes, aspect ratio 10-30, inner diameter 10nm-20nm;
[0065] Alumina, particle size 20nm~50nm;
[0066] The structural formula of octamaleamic acid cage-shaped silsesquioxane is as follows:
[0067]
[0068] Example 1
[0069] This embodiment is a high temperature resistant diaphragm for lithium battery. The cross-sectional results are as follows Figure 1 As shown, it includes a polypropylene diaphragm body 100 (Celgard2500, thickness is 25 μm);
[0070] A first modified layer 101 is provided on one side of the polypropylene diaphragm body 100;
[0071] A second modified layer 102 is provided on the other side of the polypropylene diaphragm body 100;
[0072] The first modified layer 101 includes the following raw materials:
[0073] 100 parts of polyimide (soluble polyimide, PY5006T, Suzhou Pinyu Optoelectronics Technology Co., Ltd.), 5 parts of cage-type polysilsesquioxane (octamaleamic acid cage-type silsesquioxane), 2 parts of alumina and 3 parts of silica fiber;
[0074] The second modified layer 102 includes the following preparation materials:
[0075] Polyethylene terephthalate (M W 150,000) 100 parts, arginine-modified carbon nanotubes 15 parts and zirconium oxide (D50 is 30 nm) 4 parts.
[0076] The method for preparing the high temperature resistant separator for lithium battery in this embodiment comprises the following steps:
[0077] S1. Preparing a first modified slurry and a second modified slurry:
[0078] First modified slurry:
[0079] The polyimide, cage-type polysilsesquioxane, alumina, silica fiber and solvent (the volume ratio of N,N-dimethylacetamide (DMAC) to methylpyrrolidone (NMP) is 8:2, and the mass ratio of the solvent to the polyimide is 5:1) are uniformly mixed to prepare a first modified slurry;
[0080] Second modified slurry:
[0081] Polyethylene terephthalate (MW is 150,000), arginine-modified carbon nanotubes, zirconium oxide and solvent (the volume ratio of trifluoroacetic acid / dichloromethane is 8:2; the mass ratio of polyethylene terephthalate to the solvent is 1:5), to prepare a second modified slurry;
[0082] S2, attaching the first modified slurry (4 mL) to one side of a polypropylene diaphragm body (width 20 cm*length 30 cm) by electrospinning to obtain a first modified layer;
[0083] The spinning parameters are:
[0084] The relative humidity was 40% and the injection speed was 0.1 mm / min;
[0085] The spinning voltage was 8 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0086] The second modified slurry (4 mL) was attached to the other side of the polypropylene diaphragm body by electrospinning and placed at 25° C. for 48 hours to obtain a high temperature resistant diaphragm for lithium batteries.
[0087] The spinning parameters are:
[0088] The relative humidity was 40% and the injection speed was 0.19 mm / min;
[0089] The spinning voltage was 9 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0090] The method for preparing the silica fiber in this embodiment comprises the following steps:
[0091] S1, PVA ( PVA-210) was dissolved in water (the dissolving temperature was 90°C and the dissolving time was 3h) to obtain a PVA solution (the mass fraction of the PVA solution was 12%);
[0092] TEOS (tetraethoxysilane), H3PO4, and H2O were mixed in a molar ratio of 1:0.01:11, and stirred at 25°C for 12 h to obtain SiO2 sol;
[0093] The PVA solution and SiO2 sol were mixed in a mass ratio of 1:1 and stirred at 1000 r / min for 4 h to obtain an electrospinning solution.
[0094] S2, spinning the electrospinning solution in an electrospinning machine, the parameters of the spinning process are as follows:
[0095] The relative humidity was 40% and the spinning solution injection speed was 0.05 mm / min;
[0096] The spinning voltage was 17 kV, the receiving distance was 25 cm, and the temperature was 25°C.
[0097] After spinning, the spinning product was placed in an oven at 80°C for 2 hours to dry out the moisture to obtain an electrospinning product.
[0098] S3. High temperature calcination
[0099] The electrospinning product was heated to 700°C at a heating rate of 1°C / min and kept warm for 3 hours to obtain silica fibers.
[0100] Example 2
[0101] This embodiment is a high temperature resistant diaphragm for lithium battery, which is different from the embodiment 1 in that:
[0102] The first modified layer 101 includes the following raw materials:
[0103] 100 parts of polyimide (soluble polyimide, PY5006T, Suzhou Pinyu Optoelectronics Technology Co., Ltd.), 4 parts of cage-type polysilsesquioxane (octamaleamic acid cage-type silsesquioxane), 3 parts of aluminum oxide and 2 parts of silica fiber;
[0104] The second modified layer 102 includes the following preparation materials:
[0105] Polyethylene terephthalate (M W 150,000) 100 parts, arginine-modified carbon nanotubes 10 parts and zirconium oxide (D50 is 30 nm) 5 parts.
[0106] The preparation method of the diaphragm in this example is carried out with reference to Example 1.
[0107] Example 3
[0108] This embodiment is a high temperature resistant diaphragm for lithium battery, which is different from the embodiment 1 in that:
[0109] The first modified layer 101 includes the following raw materials:
[0110] 100 parts of polyimide (soluble polyimide, PY5006T, Suzhou Pinyu Optoelectronics Technology Co., Ltd.), 6 parts of cage-type polysilsesquioxane (octamaleamic acid cage-type silsesquioxane), 1 part of aluminum oxide and 4 parts of silica fiber;
[0111] The second modified layer 102 includes the following preparation materials:
[0112] Polyethylene terephthalate (M W 150,000) 100 parts, arginine-modified carbon nanotubes 20 parts and zirconium oxide (D50 is 30 nm) 3 parts.
[0113] The preparation method of the diaphragm in this example is carried out with reference to Example 1.
[0114] Example 4
[0115] This embodiment is a high temperature resistant diaphragm for lithium battery, which is different from the embodiment 1 in that:
[0116] The first modified layer 101 includes the following raw materials:
[0117] 100 parts of polyimide (soluble polyimide, PY5006T, Suzhou Pinyu Optoelectronics Technology Co., Ltd.), 6 parts of cage-type polysilsesquioxane (octamaleamic acid cage-type silsesquioxane), 3 parts of aluminum oxide and 4 parts of silica fiber;
[0118] The second modified layer 102 includes the following preparation materials:
[0119] Polyethylene terephthalate (M W 150,000) 100 parts, arginine-modified carbon nanotubes 20 parts and zirconium oxide (D50 is 30 nm) 5 parts.
[0120] The preparation method of the diaphragm in this example is carried out with reference to Example 1.
[0121] Example 5
[0122] This embodiment is a high temperature resistant diaphragm for lithium battery, which is different from the embodiment 1 in that:
[0123] The first modified layer 101 includes the following raw materials:
[0124] 100 parts of polyimide (soluble polyimide, PY5006T, Suzhou Pinyu Optoelectronics Technology Co., Ltd.), 4 parts of cage-type polysilsesquioxane (octamaleamic acid cage-type silsesquioxane), 1 part of aluminum oxide and 2 parts of silica fiber;
[0125] The second modified layer 102 includes the following preparation materials:
[0126] Polyethylene terephthalate (M W 150,000) 100 parts, arginine-modified carbon nanotubes 10 parts and zirconium oxide (D50 is 30 nm) 3 parts.
[0127] The preparation method of the diaphragm in this example is carried out with reference to Example 1.
[0128] Comparative Example 1
[0129] This comparative example is a separator for lithium batteries, which differs from Example 5 in that:
[0130] The first modified layer 101 includes the following raw materials:
[0131] 100 parts of polyimide (soluble polyimide, PY5006T, Suzhou Pinyu Optoelectronics Technology Co., Ltd.), 1 part of alumina and 2 parts of silica fiber.
[0132] The preparation method of the lithium battery separator in this comparative example consists of the following steps:
[0133] S1. Preparing a first modified slurry and a second modified slurry:
[0134] First modified slurry:
[0135] The polyimide, alumina, silica fiber and solvent (the volume ratio of N,N-dimethylacetamide (DMAC) to methyl pyrrolidone (NMP) is 8:2, and the mass ratio of the solvent to the polyimide is 5:1) are uniformly mixed to prepare a first modified slurry;
[0136] Second modified slurry:
[0137] Polyethylene terephthalate (M W is 150,000), arginine-modified carbon nanotubes, zirconium oxide and solvent (the volume ratio of trifluoroacetic acid / dichloromethane is 8:2; the mass ratio of polyethylene terephthalate to the solvent is 1:5), to prepare a second modified slurry;
[0138] S2, attaching the first modified slurry (4 mL) to one side of a polypropylene diaphragm body (width 20 cm*length 30 cm) by electrospinning to obtain a first modified layer;
[0139] The spinning parameters are:
[0140] The relative humidity was 40% and the injection speed was 0.1 mm / min;
[0141] The spinning voltage was 8 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0142] The second modified slurry (4 mL) was attached to the other side of the polypropylene diaphragm body by electrospinning and placed at 25° C. for 48 hours to obtain a high temperature resistant diaphragm for lithium batteries.
[0143] The spinning parameters are:
[0144] The relative humidity was 40% and the injection speed was 0.19 mm / min;
[0145] The spinning voltage was 9 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0146] Comparative Example 2
[0147] This comparative example is a separator for lithium batteries, which differs from Example 5 in that:
[0148] The second modified layer 102 includes the following preparation materials:
[0149] Polyethylene terephthalate (M W 150,000) 100 parts and zirconium oxide (D50 is 30 nm) 3 parts.
[0150] The preparation method of the lithium battery separator in this comparative example consists of the following steps:
[0151] S1. Preparing a first modified slurry and a second modified slurry:
[0152] First modified slurry:
[0153] The polyimide, cage-type polysilsesquioxane, alumina, silica fiber and solvent (the volume ratio of N,N-dimethylacetamide (DMAC) to methylpyrrolidone (NMP) is 8:2, and the mass ratio of the solvent to the polyimide is 5:1) are uniformly mixed to prepare a first modified slurry;
[0154] Second modified slurry:
[0155] Polyethylene terephthalate (M W is 150,000), zirconium oxide and solvent (the volume ratio of trifluoroacetic acid / dichloromethane is 8:2; the mass ratio of polyethylene terephthalate to solvent is 1:5), to prepare a second modified slurry;
[0156] S2, attaching the first modified slurry (4 mL) to one side of a polypropylene diaphragm body (width 20 cm*length 30 cm) by electrospinning to obtain a first modified layer;
[0157] The spinning parameters are:
[0158] The relative humidity was 40% and the injection speed was 0.1 mm / min;
[0159] The spinning voltage was 8 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0160] The second modified slurry (4 mL) was attached to the other side of the polypropylene diaphragm body by electrospinning and placed at 25° C. for 48 hours to obtain a high temperature resistant diaphragm for lithium batteries.
[0161] The spinning parameters are:
[0162] The relative humidity was 40% and the injection speed was 0.19 mm / min;
[0163] The spinning voltage was 9 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0164] Comparative Example 3
[0165] This comparative example is a separator for lithium batteries, which differs from Example 5 in that:
[0166] The arginine-modified carbon nanotubes were replaced with carbon nanotubes.
[0167] The preparation method of the lithium battery separator in this comparative example consists of the following steps:
[0168] S1. Preparing a first modified slurry and a second modified slurry:
[0169] First modified slurry:
[0170] The polyimide, cage-type polysilsesquioxane, alumina, silica fiber and solvent (the volume ratio of N,N-dimethylacetamide (DMAC) to methylpyrrolidone (NMP) is 8:2, and the mass ratio of the solvent to the polyimide is 5:1) are uniformly mixed to prepare a first modified slurry;
[0171] Second modified slurry:
[0172] Polyethylene terephthalate (M W is 150,000), carbon nanotubes, zirconium oxide and solvent (the volume ratio of trifluoroacetic acid / dichloromethane is 8:2; the mass ratio of polyethylene terephthalate to the solvent is 1:5), to prepare a second modified slurry;
[0173] S2, attaching the first modified slurry (4 mL) to one side of a polypropylene diaphragm body (width 20 cm*length 30 cm) by electrospinning to obtain a first modified layer;
[0174] The spinning parameters are:
[0175] The relative humidity was 40% and the injection speed was 0.1 mm / min;
[0176] The spinning voltage was 8 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0177] The second modified slurry (4 mL) was attached to the other side of the polypropylene diaphragm body by electrospinning and placed at 25° C. for 48 hours to obtain a high temperature resistant diaphragm for lithium batteries.
[0178] The spinning parameters are:
[0179] The relative humidity was 40% and the injection speed was 0.19 mm / min;
[0180] The spinning voltage was 9 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0181] Comparative Example 4
[0182] This comparative example is a separator for lithium batteries, which differs from Example 5 in that:
[0183] The silica fibers were replaced with silica powder (D50 of 30 nm).
[0184] The preparation method of the lithium battery separator in this comparative example consists of the following steps:
[0185] S1. Preparing a first modified slurry and a second modified slurry:
[0186] First modified slurry:
[0187] The polyimide, cage-type polysilsesquioxane, alumina, silica powder and solvent (the volume ratio of N,N-dimethylacetamide (DMAC) to methylpyrrolidone (NMP) is 8:2, and the mass ratio of the solvent to the polyimide is 5:1) are mixed uniformly to prepare a first modified slurry;
[0188] Second modified slurry:
[0189] Polyethylene terephthalate (M W is 150,000), arginine-modified carbon nanotubes, zirconium oxide and solvent (the volume ratio of trifluoroacetic acid / dichloromethane is 8:2; the mass ratio of polyethylene terephthalate to the solvent is 1:5), to prepare a second modified slurry;
[0190] S2, attaching the first modified slurry (4 mL) to one side of a polypropylene diaphragm body (width 20 cm*length 30 cm) by electrospinning to obtain a first modified layer;
[0191] The spinning parameters are:
[0192] The relative humidity was 40% and the injection speed was 0.1 mm / min;
[0193] The spinning voltage was 8 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0194] The second modified slurry (4 mL) was attached to the other side of the polypropylene diaphragm body by electrospinning and placed at 25° C. for 48 hours to obtain a high temperature resistant diaphragm for lithium batteries.
[0195] The spinning parameters are:
[0196] The relative humidity was 40% and the injection speed was 0.19 mm / min;
[0197] The spinning voltage was 9 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0198] Comparative Example 5
[0199] This comparative example is a separator for lithium batteries, which differs from Example 5 in that:
[0200] The first modified layer 101 includes the following raw materials:
[0201] 100 parts of polyimide (soluble polyimide, PY5006T, Suzhou Pinyu Optoelectronics Technology Co., Ltd.), 1 part of alumina and 2 parts of silica fiber;
[0202] The second modified layer 102 includes the following preparation materials:
[0203] Polyethylene terephthalate (M W 150,000) 100 parts and zirconium oxide (D50 is 30 nm) 3 parts.
[0204] The preparation method of the lithium battery separator in this comparative example consists of the following steps:
[0205] S1. Preparing a first modified slurry and a second modified slurry:
[0206] First modified slurry:
[0207] The polyimide, alumina, silica fiber and solvent (the volume ratio of N,N-dimethylacetamide (DMAC) to methyl pyrrolidone (NMP) is 8:2, and the mass ratio of the solvent to the polyimide is 5:1) are uniformly mixed to prepare a first modified slurry;
[0208] Second modified slurry:
[0209] Polyethylene terephthalate (M W is 150,000), zirconium oxide and solvent (the volume ratio of trifluoroacetic acid / dichloromethane is 8:2; the mass ratio of polyethylene terephthalate to solvent is 1:5), to prepare a second modified slurry;
[0210] S2, attaching the first modified slurry (4 mL) to one side of a polypropylene diaphragm body (width 20 cm*length 30 cm) by electrospinning to obtain a first modified layer;
[0211] The spinning parameters are:
[0212] The relative humidity was 40% and the injection speed was 0.1 mm / min;
[0213] The spinning voltage was 8 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0214] The second modified slurry (4 mL) was attached to the other side of the polypropylene diaphragm body by electrospinning and placed at 25° C. for 48 hours to obtain a high temperature resistant diaphragm for lithium batteries.
[0215] The spinning parameters are:
[0216] The relative humidity was 40% and the injection speed was 0.19 mm / min;
[0217] The spinning voltage was 9 KV, the receiving distance was 15 cm, and the temperature was 25°C.
[0218] The performance of the diaphragms prepared in the above examples and comparative examples was tested, and the results are shown in Table 1. The test items are as follows:
[0219] Membrane breaking temperature:
[0220] The film breaking temperature is measured by the resistance mutation method, and the point where the resistance suddenly increases is the film breaking temperature;
[0221] Heat shrinkage test:
[0222] Cut the membrane to be tested into a 3cm×3cm square test sample and sandwich the sample between two glass sheets. Heat the oven to the set temperature (200℃) and keep it warm for 30 minutes. Place the sample in the oven and heat it for 30 minutes. The shrinkage rate is calculated by the following equation:
[0223] Thermal shrinkage (%) = 100 × (Ai-Af) / Ai;
[0224] where Ai and Af are the initial and final areas of the relevant diaphragm, respectively.
[0225] Table 1
[0226] - Membrane breaking temperature (℃) Thermal shrinkage (%) Example 1 293 0.12 Example 2 287 0.18 Example 3 280 0.21 Example 4 289 0.17 Example 5 276 0.23 Comparative Example 1 253 1.62 Comparative Example 2 257 1.53 Comparative Example 3 259 1.49 Comparative Example 4 268 0.56 Comparative Example 5 250 2.36
[0227] It can be seen from Table 1 that the diaphragms in Examples 1 to 5 have high film breaking temperatures and low thermal shrinkage rates; they have excellent high temperature resistance, which is beneficial to improving the safety performance of lithium batteries.
[0228] In Comparative Example 1, no cage-type polysilsesquioxane is added; the dispersion effect of the inorganic particles in the polyimide is poor, resulting in poor thermal stability of the diaphragm.
[0229] In Comparative Example 2, no arginine-modified carbon nanotubes were added; a point-line heat-insulating network could not be constructed, resulting in poor thermal stability of the diaphragm.
[0230] In Comparative Example 3, the arginine-modified carbon nanotubes were replaced with carbon nanotubes; the dispersion effect of the inorganic particles was poor, resulting in poor thermal stability.
[0231] In Comparative Example 4, the silica fiber was replaced with silica powder; a point-line thermal insulation network could not be constructed, resulting in poor thermal stability of the diaphragm.
[0232] In Comparative Example 5, cage-type polysilsesquioxane and arginine-modified carbon nanotubes are not added; the dot-line thermal insulation network cannot be constructed in the second modified layer and the inorganic particles in the first modified layer have a poor dispersion effect, resulting in poor thermal stability of the diaphragm.
[0233] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A high temperature resistant diaphragm for lithium battery, It is characterized in that including a polypropylene diaphragm body; A first modified layer is provided on one side of the polypropylene diaphragm body; A second modified layer is provided on the other side of the polypropylene diaphragm body; The first modified layer includes the following preparation materials: Polyimide, cage-type polysilsesquioxane, alumina, and silica fibers; The second modified layer includes the following preparation materials: Polyethylene terephthalate, arginine-modified carbon nanotubes, and zirconium oxide.
2. The high temperature resistant separator for lithium battery according to claim 1, It is characterized in that The first modified layer comprises the following raw materials in parts by weight: 100 parts of polyimide, 4 to 6 parts of cage-type polysilsesquioxane, 1 to 3 parts of aluminum oxide and 2 to 4 parts of silicon dioxide fiber; And / or, the raw materials for preparing the first modified layer further include a solvent.
3. The high temperature resistant separator for lithium battery according to claim 1, It is characterized in that The second modified layer includes the following raw materials in parts by weight: 100 parts of polyethylene terephthalate, 10 to 20 parts of arginine-modified carbon nanotubes and 3 to 5 parts of zirconium oxide; And / or, the raw material for preparing the second modified layer further includes a solvent.
4. The high temperature resistant separator for lithium battery according to claim 1, It is characterized in that The thickness of the polypropylene diaphragm body is 5 μm to 30 μm.
5. The high temperature resistant separator for lithium battery according to claim 1, It is characterized in that The arginine-modified carbon nanotubes include the following preparation raw materials: Carbon nanotubes, nitric acid, thionyl chloride, and arginine.
6. The high temperature resistant separator for lithium battery according to claim 1, It is characterized in that The particle size of the aluminum oxide is 20nm to 50nm.
7. The high temperature resistant separator for lithium battery according to claim 1, It is characterized in that The silica fiber comprises the following preparation raw materials: PVA solution and silica sol; And / or, the mass fraction of the PVA solution is 11% to 13%; And / or, the raw materials for preparing the silica sol include tetraethoxysilane and a catalyst; And / or, the mass ratio of the PVA solution to the silica sol is 1:0.9-1.
1.
8. A method for preparing a high temperature resistant separator for a lithium battery according to any one of claims 1 to 7, It is characterized in that The following steps are involved: The first modified layer and the second modified layer are formed on the surface of the polypropylene diaphragm body by using an electrostatic spinning method.
9. The preparation method according to claim 8, It is characterized in that The method for preparing the arginine-modified carbon nanotubes comprises the following steps: S1, mixing carbon nanotubes and nitric acid solution and subjecting them to hydrothermal reaction to obtain carboxylated carbon nanotubes; S2, mixing the carboxylated carbon nanotubes and thionyl chloride and reacting them to obtain acyl chloride carbon nanotubes; S3, mixing the acyl chloride carbon nanotubes, arginine, dicyclohexylcarbodiimide and a solvent and reacting them; and / or, the mass volume ratio of the carbon nanotubes to the nitric acid solution is 1 g: 50 mL to 100 mL; And / or, the temperature of the hydrothermal reaction in step S1 is 110° C. to 130° C.; and / or, the mass volume ratio of the carboxylated carbon nanotubes to thionyl chloride is 1 g: 100 mL to 200 mL; And / or, the reaction temperature in step S2 is 80°C to 90°C; And / or, the mass ratio of the acyl chloride carbon nanotubes to arginine is 1:1-2; And / or, the mass ratio of the acyl chloride carbon nanotubes to dicyclohexylcarbodiimide is 1:0.2-0.3; And / or, the reaction temperature in step S3 is 60°C to 70°C.
10. The preparation method according to claim 8, It is characterized in that The spinning voltage selected in the electrostatic spinning method is 5 kV to 10 kV.
Citation Information
Patent Citations
Nano silicon dioxide reinforced PP material and preparation process thereof
CN113278225A
Lithium ion battery diaphragm slurry, preparation method thereof and lithium ion battery diaphragm
CN114497897A
High-ionic-conductivity composite lithium battery diaphragm and preparation method thereof
CN116365171A
Silsesquioxane ceramic coating diaphragm as well as preparation method and application thereof
CN116544606A
High-temperature-resistant polymer diaphragm and preparation method thereof
CN117080675A
Cited By
High-heat-resistance battery diaphragm and preparation method of battery
CN120453626A
High-safety diaphragm for new energy battery and preparation method of high-safety diaphragm
CN120566001A
